Effectiveness of My Alazka Application Learning Media in Improving Student’ Chemistry Learning Outcomes - Wahjusaputri, Sintha; Ramadhani, Siti Sarah; Saepudin, Asep; Reihan, Muhammad; Suryanto, Hendi (Universitas Negeri Surabaya, 2023)
Objective: This research aims to determine, analyze, and identify the effectiveness of the My Alazka Application learning media on the chemistry learning outcomes of 10th grade pupils. Method: This study used a quantitative method for experimental research. The subject of this study was a 28 Student in 10th grade, in accordance to the pretest-posttest design with a single group. This research uses instruments such as questionnaires that are used once before the investigation, known as the pre-test, and once after the experiment, known as the post-test. Result: Based on the Descriptive N-Gain Score data output, The data indicates the mean N-Gain score among students in 10th grade is 63.3074 or 0.63 which is included in the